2020
DOI: 10.1038/s42003-020-01250-3
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected mutual regulation underlies paralogue functional diversification and promotes epithelial tissue maturation in Tribolium

Abstract: Insect Hox3/zen genes represent an evolutionary hotspot for changes in function and copy number. Single orthologues are required either for early specification or late morphogenesis of the extraembryonic tissues, which protect the embryo. The tandemly duplicated zen paralogues of the beetle Tribolium castaneum present a unique opportunity to investigate both functions in a single species. We dissect the paralogues’ expression dynamics (transcript and protein) and transcriptional targets (RNA-seq after RNAi) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(59 citation statements)
references
References 85 publications
(144 reference statements)
4
55
0
Order By: Relevance
“…This corroborates the accuracy of the original, nested amplicon for quantification of Tc-zen1 transcript levels. Moreover, these findings with either amplicon are consistent with our previous work that documented a single early pulse of Tc-zen1 expression that peaks at 6-10 h before rapidly declining to undetectable levels for the rest of embryogenesis [20].…”
Section: Results Dsrna Is Transported Into Eggs and Persists During Embryogenesissupporting
confidence: 91%
See 4 more Smart Citations
“…This corroborates the accuracy of the original, nested amplicon for quantification of Tc-zen1 transcript levels. Moreover, these findings with either amplicon are consistent with our previous work that documented a single early pulse of Tc-zen1 expression that peaks at 6-10 h before rapidly declining to undetectable levels for the rest of embryogenesis [20].…”
Section: Results Dsrna Is Transported Into Eggs and Persists During Embryogenesissupporting
confidence: 91%
“…The homeodomain transcription factor Tc-Zen1 is a critical regulator in early development, specifying the identity of the extraembryonic serosal tissue that surrounds the embryo and confers mechanical, physiological, and immunological protection [18,20,26,27]. During routine verification of Tc-zen1 parental RNAi using RT-qPCR (as in [20]), we unexpectedly found that measured expression of Tc-zen1 mRNA was higher in RNAi samples than in wild type under certain assay conditions, despite strong phenotypic validation of systemic knockdown (see Methods).…”
Section: Results Dsrna Is Transported Into Eggs and Persists During Embryogenesismentioning
confidence: 99%
See 3 more Smart Citations